PENGEMBANGAN SAMSAK UNTUK MENINGKATKAN KEMAMPUAN TEKNIK BERTARUNG PADA EKSKUL TARUNG DERAJAT DI SEKOLAH MENENGAH ATAS - Halomoan, Rinaldi; Hariadi, Hariadi (Indonesia Sport Journal, 2024)
The purpose of this study is to develop training media in improving the ability of fighting techniques in Tarung Derajat extracurricular activities. Tarung This research was first validated by material experts and media experts. The product trial was carried out on extracurricular fighting students at SMA Plus Sedayu Nusantara with a population of 25 students. Small group test of 7 students, and large group test of 18 students. Type of data collection with a questionnaire instrument. The method used is Research and Development (R&D). The results showed that the developed tools were feasible. These results were obtained from the validation of (a) material experts by 92% or very feasible; (b) media expert of 91.4 or very decent; (c) small group trial of 81.6% or feasible; (d) large group trial of 92.8% or Very Eligible. Thus, the product produced in this development is a tarung bag. This training tool has been declared suitable to be used as a training medium in improving the ability of fighting techniques in Tarung Derajat extracurricular activities.